(untitled) (The International Research Journal of Management Science, 2016)
This survey aimed at ascertaining the views of 120 respondents from overall sectors on the factors that determine the awareness in life insurance in the context of Nepal. The result of insurance awareness hypothesis shows that education is an important factor which affects the buying decision of consumers in life insurance. The researcher has employed descriptive design to conduct the study through structured set of questionnaire; convenience sampling technique has been used in the initial stage to narrow down the population from entire population. Similarly likert scale has been used for consumer survey and later computed using statistical package for social science (SPSS) Version 20 for windows to compare means. The survey result produces the result that in spite of the immense benefits and security provided by the life insurance, public awareness regarding it is low. The research also provides light in the aspect that insurance awareness is positively affected by educational level of attainment whereas it is statistically independent to gender, income and professional line of involvement.